A Cohort Study of Patient-Reported Outcomes and Healthcare Utilization in Acute Myeloid Leukemia Patients Receiving Active Cancer Therapy in the Last Six Months of Life - Lowe, Jared R. (J Palliat Med, 2018)
Background: Evidence about the unique palliative care needs of patients with acute myeloid leukemia (AML) is limited. Improving the care of these patients will require a better understanding of their unmet needs, including symptom burden at the end of life, and patterns of healthcare utilization. Objective: To describe AML patients' experiences in the last six months of life regarding symptom burden, blood product utilization, and use of palliative care services. Methods: Exploratory analysis of prospectively collected patient-reported outcomes and healthcare utilization data during the last six months of life among 33 AML patients who died during a longitudinal observational study. Results: Symptom burden, quality of life (QOL), and psychological distress worsened with proximity to death. Of the 26 patients with utilization data, most (n = 24; 92.4%) were hospitalized in the last month of life, with 26.9% (n = 7) dying in the intensive care unit. Patients required a median of 16 red blood cell transfusions in the last six months of life, and those with a high transfusion burden in the last month of life had a higher rate of in-hospital death (blood transfusions: p < 0.01; platelet transfusions: p = 0.03). Only six patients enrolled in hospice (23.1%). Discussion: Patients with AML have marked symptoms and QOL impairments that escalate in the final six months of life. Patients entering the healthcare system for active cancer treatment are likely to continue disease-oriented care until death. High rates of hospitalization and blood product transfusion are a direct barrier to transitioning to hospice care.